Pseudospin-electron model spectrum in alloy analogy approximation - Stasyuk, I.V.; Krasnov, V.O. (Condensed Matter Physics, 2006)
Energy spectrum of the pseudospin-electron model is investigated in the alloy analogy approximation within the framework of the dynamical mean field theory (DMFT). The case of two near Hubbard-like electron subbands, which determine the location of chemical potential at a certain set of model parameter values, is considered. The conditions of gap appearance in the spectrum are established. The effect of the asymmetry field h and tunneling-like splitting of levels in the local anharmonic well on the critical value Ucrit of the on-site Hubbard interaction constant is investigated. Дослiджено спектр псевдоспiн-електронної моделi у наближеннi сплаву при використаннi методу динамiчного середнього поля (ДСП). Дослiджується випадок двох близьких зон хаббардiвського типу, що визначають положення хiмiчного потенцiалу при заданих параметрах моделi. Розглянуто умови появи щiлини в спектрi. Дослiджено вплив поля асиметрiї h та тунельного розщеплення рiвнiв на критичне значення вузлової хаббардiвської константи взаємодiї Ucrit.